2010
DOI: 10.1509/jmkr.47.3.553
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Need for Uniqueness on Word of Mouth

Abstract: positive WOM can decrease the uniqueness of one's possessions, which hurts high-uniqueness individuals (pilot study). As a result, high-(vs. low-) uniqueness individuals are less willing to generate positive WOM for publicly consumed products that they own. However, high uniqueness does not decrease willingness to generate WOM for privately consumed products (study 1). Study 2 demonstrates that for publicly consumed products, WOM that includes positive recommendations is perceived to be more persuasive than WO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
269
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 336 publications
(281 citation statements)
references
References 35 publications
8
269
2
2
Order By: Relevance
“…Indeed, WOM has a stronger power to impact on consumers compared with other communication channels (Bansal & Voyer, 2000), while consumers tend to rely on others' advice to make purchase decisions (Cheema & Kaikati, 2010). Furthermore, WOM is also perceived as a reliable source since Bansal and Voyer (2000) found out that people who often perceive risk and were not confident in their knowledge tend to search for more WOM information.…”
Section: Word-of-mouthmentioning
confidence: 99%
“…Indeed, WOM has a stronger power to impact on consumers compared with other communication channels (Bansal & Voyer, 2000), while consumers tend to rely on others' advice to make purchase decisions (Cheema & Kaikati, 2010). Furthermore, WOM is also perceived as a reliable source since Bansal and Voyer (2000) found out that people who often perceive risk and were not confident in their knowledge tend to search for more WOM information.…”
Section: Word-of-mouthmentioning
confidence: 99%
“…The aim of one of the marketing communication traditional elements, «Word-of-Mouth» (hereinafter referred to as WOM), was to spread good name of the company, its brands, products based on the positive experience with it, to share this experience with the family, relatives, friends, and all that in an uncontrolled and spontaneous way. A. Cheema and A. Kaikati argue that information sharing is a key element of marketing communication process, because consumers tend to rely on the advice and recommendations of others when making purchasing decisions, particularly in si tuations that are financially or psychologically risky for them [13,556]. It has been demonstrated that WOM presents a more effective way of disseminating ideas than a spread of the communication message through traditional media.…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…When such conflicting feelings occur, individuals seek different ways to alleviate such spontaneous stress. Researchers such as Cheema and Kaikati (2010) have found evidence that one of the best ways to reduce the discomfort of cognitive dissonance after buying a product is to share the conflicting experience with others. The Internet is currently a convenient channel for sharing emotions and experiences with others.…”
Section: Literature Review and Conceptual Developmentmentioning
confidence: 99%